The Interplay among Green Human Resource Practices, Organization Citizenship Behavior for Environment and Sustainable Corporate Performance Evidence from Jordan - Alnajdawi, Sakher; Emeagwali, Okechukwu Lawrence; Elrehail, Hamzah (Journal of Environmental Accounting and Management, 2026)
Green environment need green practices, so for that the researchers conduct this study to investigate the Green Human Resources Management (GHRM) practices on Sustainable Corporate Performance (SCP) through mediating role of Organization Citizenship Behavior for Environment (OCBE). The finding of this study reveals that GHRM has a positive impact on SCP through the mediator OCBE in the “Manaseer Group” in Jordan. Moreover, this study has its theoretical contribution by applying this study in Middle East and North Africa (MENA) region and enriches literature by new evidences that GHRM could enhance SCP. Using Structural Equation Modeling (SEM) approach for analysis purpose with 318 questionnaires collected from responder of the study disrupted among “Manaseer Group”.